Digital serious games in developing nursing clinical competence: A systematic review and meta-analysis. (June 2022) - Thangavelu, Dhivya P.; Tan, Apphia J.Q.; Cant, Robyn; Chua, Wei Ling; Liaw, Sok Ying
Abstract: Objective: This review aimed to synthesise evidence from experimental studies of the application of digital serious games in developing nursing clinical competence. Design: Systematic review and meta-analysis. Data sources: Eight databases were searched for randomized controlled trials and quasi-experimental studies published in English from 2000 to 2021. Review methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were adopted in this review. Quality appraisal was conducted using Cochrane's Risk of Bias tool and the Joanna Brigg's Institute Critical Appraisal Tool for Quasi-Experimental Designs. A narrative synthesis of studies, and a meta-analysis and subgroup analysis, was performed on the study outcomes. Results: 22 experimental studies including 13 randomized controlled trials and nine quasi-experimental studies were included. Of these, 19 studies examined nursing students and three examined qualified nurses. These studies applied serious games to develop nursing competencies in management of nursing care, clinical reasoning skills, procedural skills, legal practice and quality improvement. Compared with control groups, serious games improved knowledge (SMD = 1.30, 95% CI [0.75, 1.86]) and skills (SMD = 0.38, 95% CI [0.17, 0.60]). Subgroup analysis for both knowledge and skills outcomes demonstrated that serious games were more effective than control groups with either no intervention or other educational interventions. A large effect size (SMD = 1.13, 95% CI [0.91, 1.34]) was found in favour of serious games for improving knowledge scores in management of nursing care. Conclusion: The reviewed studies identified a broad application of digital serious games for developing nursing competencies. The knowledge and skills performance outcomes supported the use of serious games, which were found to be superior to conventional educational interventions. More serious games are required to be incorporated into undergraduate and continuing nursing education for workplace training, with more rigorous studies examining the effect of serious games in improving the quality and safety of clinical nursing practice. Highlights: Digital serious games contribute to nursing competence development. Digital serious games positively impact nurses' knowledge and skill development. Digital serious games are feasible for undergraduate and continuing nursing education. Future studies to incorporate competence development of communication and teamwork Necessary to evaluate effectiveness of digital serious games in real clinical environments